Clinical features of HIV/AIDS and various opportunistic infections in relation to antiretroviral status among HIV seropositive individuals from Central Nepal - Sharma, S; Dhungana, GP; Pokharel, BM; Rijal, BP (Kathmandu University Medical Journal, 2010)
Background: So far, antiretroviral therapy is the only effective treatment available to HIV/AIDS patients. Provision of combined package of treatment, care and support service as well as regular assessment of the therapy increases its effectiveness. Objective: The aim of this study was to establish the relationship between antiretroviral therapy status and clinical features/opportunistic infections among HIV seropositive individuals. Materials and methods: This is a cross-sectional study. Study was carried out between October 2007 and May 2008 in 150 HIV patients of Kathmandu, Central Nepal. After taking informed consent pre-structured questionnaire was filled to assess clinical features and specimen were collected to investigate major OIs as per standard microbiological procedure. All the information were entered into SPSS 11.5 system and analysed. Result: Of the 150 patients, 100 (66.7%) were males and 50 (33.3%) were females. The age group 21-30 years was predominant followed by 31-40 years (42%). Significant relationship could be established between intake of ART and cardinal symptoms of HIV/AIDS (χ2 value ranging from 4.11 to 9.34). However, no significant relationship could be established between the intake of ART and distribution of different OIs (χ2 values ranging from 0.15 to 1.6). Conclusion: Antiretroviral therapy was found to effective enough to reduce the clinical features of AIDS. Diagnosis and treatment of opportunistic infections should be routinely done for both groups of patients. Key words: Antiretroviral therapy; CD4 count; HIV/AIDS; Nepal DOI: 10.3126/kumj.v7i4.2754 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 355-359